Predicting millennial farmer success by highlighting the role of digitalization and technology in increasing productivity - Hutapea, Yanter; Prasetyo, Andjar; Yardha,; Minsyah, Nur Imdah; Wamaer, Demas; Suharyon,; Tarmizi, Achmad; Wulandari, Sekar Nur; Septiyarini, Dwi; Adi, Ari Sasmoko (Frontiers in Sustainable Food Systems, 2025)
This study aims to analyze the main factors that affect the success of millennial farmers in increasing quantity in Indonesia. This study uses a quantitative approach with the K-Nearest Neighbors Regression model to predict the success of millennial farmers based on three main factors, infrastructure, business dynamism, and the adoption of information and communication technology. Secondary data was collected from the conversion index of the number of millennial farmers aged 39+ years who use digital and modern technology, for the three main factors of the regional competitiveness index in 34 provinces with analysis based on Mean Squared Error and Mean Dropout Loss. The results show that infrastructure (0.101) and business dynamism (0.099) have the greatest impact on the success of millennial farmers, while technology adoption (0.025) contributes less. While digitalization is important, its effectiveness depends on the readiness of the infrastructure and supporting business ecosystems. Theoretically, this research enriches the literature on digital transformation in agriculture. In practical terms, these results confirm the need for infrastructure investment and policies that support business innovation so that digitalization has an optimal impact on millennial farmers.